PERAWATAN PERMESINAN KAPAL PURSE SEINE UNTUK MENUNJANG KELANCARAN PELAYARAN KOMUNITAS NELAYAN PURSE SEINE TAWANG KENDAL - Mohammad Sapta Heriyawan; Zaenal Arifin, Moh. (Pengabdian Masyarakat, 2024)
Purse Seine Boat Fishermen are fishermen who sail using boats with fishing gear whose main tool is a net, used to catch large fish or small fish according to their size and number. The fishing Tawang community as a source of livelihood in fishing needs to be equipped with expertise in the field of maintaining ship machinery as vehicles used by fishermen for fishing to get to fishing grounds and operating fishing equipment, especially purse seines. The success of a fishing vessel is if it fulfills 3 (three) factors, namely seaworthiness, operation worthiness and storage worthiness. Seaworthiness greatly influences the performance of a ship at sea, including the ship's machinery. Care must be taken to maintain the machinery so that it supports smooth seaworthiness and supports operational feasibility. For this reason, in order to support this, the Maritime Science Polytechnic is implementing the Tri Dharma of Higher Education Community Service, socialization regarding purse seine ship machinery maintenance for the purse seine ship fishermen community, Gempol Sewu Village, Kendal Regency.